Article Review Case Analysis of Post-Placenta IUD Expulsion - Evi Nurhidayati; Dewi Setyoningsih (International Journal of Health Science and Technology, 2020)
Indonesian Government has launched various programs to overcome population problems. Postpartum Family planning program is included in maternal insurance program, so every partum mother can immediately insert Post-placenta IUD for free. The failure of inserting IUD contraception in Indonesia reached 37.75%. The result of this review can be taken into consideration regarding goverment policy about Postpartum Family Planing Programe.  The design of this study is literature review. The selected articles are those relating to IUD Post-placenta expulsion. Database PubMed used to cellecting article. We only take article that published from 2010 – 2018. The analysis of 11 journals showed that the IUD post-placenta have rates of expulsion varies from some article, the lowest 1,4 % and highest 24 %. Then delayed insertion of IUD have expulsion rates 0 % up to 37%. This review supports the evidence that insertion of an IUD Postplacenta after vaginal delivery or caesarean delivery is safe. Expulsion rates should be further studied in larger randomised controlled trials.